Exploring the Interaction between Vancomycin/Teicoplanin and Receptor Binding Domain (RBD) of SARS-CoV-2 - Tao, Wen-Tao; Yu, Qian; Li, Ya-Li; Ge, Mei; Zhao, Yi-Lei; Shi, Ting (Frontiers in Chemistry, 2021)
The recent pandemic caused by SARS-CoV-2 has spread to over 100 countries, infected more than 47 million people and resulted in more than 1.2 million deaths worldwide until October. It is well known that, the SARS-CoV-2 starts an infection by binding its Receptor Binding Domain (RBD) of spike protein to human Angiotensin converting enzyme 2 (ACE2) receptor, and strenuous efforts had been made to prevent the infection. However, no successful drugs or vaccines have appeared. Herein, molecular docking and molecular simulations were carried out to study the interaction between RBD and two glycopeptide antibiotics (Vancomycin and Teicoplanin). Key residues in binding pocket were highlighted and the binding free energies were calculated. Our results suggested that Vancomycin and Teicoplanin, as natural and accepted antibiotics, could block the interaction between RBD of spike protein and human ACE2 receptor, which might be developed to potential drugs against the SARS-CoV-2.